Impact of debt and taxes on earnings persistence of Portuguese SMEs - Pereira, Cláudia; Gomes, Luís; Lima, Armindo (Review of Business Management, 2023)
Purpose – We analyze how debt burden and income taxes affect the earnings quality of Portuguese SMEs, using earnings persistence as a proxy for earnings quality. More specifically, we intend to find out whether the high indebtedness of these firms causes a greater tax effect than debt effect. Theoretical framework – While credit banks represent the main source of financing for SMEs, they tend to reduce their earnings in order to avoid taxes. However, this activity can be costly for their development, given that banking institutions demand earnings persistence to reduce the risk of default, in accordance with contract theory. Design/methodology/approach – We collect data for 140 Portuguese SMEs over the period from 2015 to 2021 to run panel data regressions. Findings – Debt and earnings persistence are negatively related, so this relationship tends to degrade earnings quality, which is inconsistent with capturing bank confidence. Furthermore, debt maintains the negative effect with income taxes in the model. However, in this combination, income taxes become significant to explain the negative influence on earnings persistence, which is consistent with tax avoidance. Finally, we control for firm size, which is positively associated with earnings persistence. Overall, taking together the determinants of debt, income tax and size, Portuguese SMEs do not have persistent earnings. Originality/value – In the most leveraged Portuguese SMEs, debt is not a governance mechanism to control managers’ decisions, as more debt reduces earnings persistence, meaning that managers are not sensitive to capturing creditors’ confidence. In addition, the tax effect is more relevant than the debt effect for earnings persistence. Faced with interest rate rigidity, managers exploit the discretionary nature of tax decisions. Keywords – SMEs; earnings persistence; debt; income taxes.